Biogenic Silver Nanoparticles Synthesized by Lysinibacillus xylanilyticus MAHUQ-40 to Control Antibiotic-Resistant Human Pathogens Vibrio parahaemolyticus and Salmonella Typhimurium - Huq, Md. Amdadul (Frontiers in Bioengineering and Biotechnology, 2020)
The present study highlights a simple and eco-friendly method for the biosynthesis of silver nanoparticles (AgNps) using Lysinibacillus xylanilyticus strain MAHUQ-40. Also, the synthesized AgNps were used to investigate their antibacterial activity and mechanisms against antibiotic resistant pathogens. Biosynthesis of AgNPs was confirmed by Ultraviolet–visible spectroscopy and then, they were characterized by field emission-transmission electron microscopy (FE-TEM), X-ray diffraction (XRD), dynamic light scattering (DLS), and Fourier transform-infrared (FTIR). The toxicity of AgNPs against two pathogenic bacteria was evaluated. The UV–vis spectral scanning showed the peak for synthesized AgNPs at 438 nm. Under FE-TEM, the synthesized AgNPs were spherical with diameter ranges from 8 to 30 nm. The XRD analysis revealed the crystallinity of synthesized AgNPs. FTIR data showed various biomolecules including proteins and polysaccharides that may be involved in the synthesis and stabilization of AgNPs. The resultant AgNPs showed significant antibacterial activity against tested pathogens. The MICs (minimum inhibitory concentrations) and MBCs (minimum bactericidal concentrations) of the AgNPs synthesized by strain MAHUQ-40 were 3.12 μg/mL and 12.5 μg/mL, respectively against Vibrio parahaemolyticus and 6.25 μg/mL and 25 μg/mL, respectively against Salmonella Typhimurium. FE-TEM analysis displayed that the biogenic AgNPs generated structural and morphological changes and damaged the membrane integrity of pathogenic bacteria. Our findings showed the potentiality of Lysinibacillus xylanilyticus MAHUQ-40 to synthesis AgNPs that acted as potent antibacterial material against pathogenic bacterial strains.